Implementasi Pupuk N, P, dan K untuk Mendukung Swasembada Kedelai - KARSIDI PERMADI (Fakultas Pertanian Universitas Udayana, 2014)
Implementation of Nitrogen, Phospahte and Potassium fertilizer for self-sufficiency insoybeans.In order to minimize import of soybean in Indonesia, soybean crop is now planted as maincrop like rice plants and maize. To gain self-sufficiency in soybeans, expansion of soybean planting areawhether in irrigated or in rainfall-dependent of rice plant area, and also multiple cropping of soybeanswith cassava may be required. Beside that, government policy in providing needs for soybean plantingsuch as fertilizers, good seeds and pesticide and also fix price of soybean in farmer level may increasea will of farmers in planting soybean. To obtain a high yield, soybean requires nutrients of N, P and Kin appropriate amounts. The needs of P and K nutrient in soil is determined with Bray-1 method ofanalysis, while dose of N fertilizer was 54 to 80 kg N ha-1.